The Role Of Sales Men In Building The Competitive Advantage Of A Retailer "Case Study Mall (City Center) In Lattakia Governorate" - نصور ريزان; ابراهيم مضر (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The study aims to analyze the impact of the role of salesmen in building the competitive advantage of retail stores. And that is by conducting a case study on the (City Center) Mall in Lattakia Governorate, where the five-way Likert scale was used in the research questionnaire, and the questionnaire was distributed to a random sample where 160 were distributed to a sample of consumers who made the purchase from the Lattakia City Center Mall And, in the analysis, statistical indicators appropriate to the nature of nominal and ranking data were used. The study reached a set of results, the most important of which were: 1- There is a significant relationship between the values, ethics and behavior of the salesman and building the competitive advantage of retail stores (City Mall) in Lattakia Governorate. 2- There is a significant relationship between the capabilities and skills of the salesman and building the competitive advantage of retail stores (City Mall) in Lattakia Governorate. 3- The effect of each dimension varies on the dimensions of the role of the men of sale in building the competitive advantage of retail stores (City Mall) in Lattakia Governorate. As it is arranged as follows, starting with the most influential ones: Values, manners and behavior of the salesman Salesman capabilities and skills The researcher also presented through this study a set of suggestions and recommendations that are expected to help the owners of retail stores to increase the effectiveness and efficiency of salesmen, which enhances the competitive position of these stores.